Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fpsyt.2020.557148
|View full text |Cite
|
Sign up to set email alerts
|

What Mediates the Relationship Between Ethnic Discrimination and Stress? Coping Strategies and Perceived Social Support of Russian Immigrants in Germany

Abstract: Objective: Experiences of ethnic discrimination may constitute major stressors for ethnic minority groups. This study examined the associations between different forms of ethnic discrimination and levels of perceived stress in Russian immigrants living in Germany, taking into account potential moderating (in-group identification) and mediating (coping and social support) factors. Methods: Russian immigrants (N = 308) were assessed using online questionnaires (e.g., perceived stress scale, behaviors from interg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 111 publications
1
17
0
Order By: Relevance
“…Our findings support the social causation model, which theorizes that experiencing discrimination damages social connections, leading to heightened psychological distress [9,10]. Other studies have also identified that race-based and mental illness-based discrimination had indirect effects on mental health outcomes through social support [10,46,47]. Although no studies to our knowledge have tested this model among HCWs, qualitative studies have identified that minority and female HCWs face discrimination in terms of social exclusion and isolation [30,48] that could prevent them from accessing the mental health benefits of social support.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings support the social causation model, which theorizes that experiencing discrimination damages social connections, leading to heightened psychological distress [9,10]. Other studies have also identified that race-based and mental illness-based discrimination had indirect effects on mental health outcomes through social support [10,46,47]. Although no studies to our knowledge have tested this model among HCWs, qualitative studies have identified that minority and female HCWs face discrimination in terms of social exclusion and isolation [30,48] that could prevent them from accessing the mental health benefits of social support.…”
Section: Discussionsupporting
confidence: 83%
“…Enriched Social Support Inventory (ESSI, Mitchell et al, 2003 ) consists of 7 items; however, we selected 6 items measuring perceived availability of social support excluding an item asking marriage status ( Goreis et al, 2020 ). The scale asks about the availability of anybody regardless of ethnic groups who can help around the individual, not specific others like partners or friends (e.g., “ Is there someone available to give you good advice about a problem?…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the mediating role of perceived social support is little investigated. Interestingly, Goreis et al (2020) identifies social support not moderating but mediating between discrimination and psychological distress among Russian immigrants in Germany. The study suggests that those who face discrimination tend to perceive social support less available, which leads to increase in distress.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Another study reported that migrant females are mostly confronted by complicated patterns of health problems associated with social deprivation and traditional cultural values, which may conflict with the host nation’s norms, and thus, results in inferior self-esteem and ambiguity of feelings 100. In this SLR, the ability to identify sociocultural risk factors among ageing migrants was limited to three studies, focusing on perceived discrimination 103 104. It is therefore important that more robust research is done to address the importance of traditions and norms for health among ageing migrants 101…”
Section: Discussionmentioning
confidence: 99%